Binding Kinetics of Ruthenium Pyrithione Chemotherapeutic Candidates to Human Serum Proteins Studied by HPLC-ICP-MS - Marković, Katarina (Molecules, 2020)
The development of ruthenium-based complexes for cancer treatment requires a variety of pharmacological studies, one of them being a drug’s binding kinetics to serum proteins. In this work, speciation analysis was used to study kinetics of ruthenium-based drug candidates with human serum proteins. Two ruthenium (Ru) complexes, namely [(η(6)-p-cymene)Ru(1-hydroxypyridine-2(1H)-thionato)Cl] (1) and [(η(6)-p-cymene)Ru(1-hydroxypyridine-2(1H)-thionato)pta]PF(6) (2) (where pta = 1,3,5-triaza-7-phosphaadamantane), were selected. Before a kinetics study, their stability in relevant media was confirmed by nuclear magnetic resonance (NMR). Conjoint liquid chromatography (CLC) monolithic column, assembling convective interaction media (CIM) protein G and diethylamino (DEAE) disks, was used for separation of unbound Ru species from those bound to human serum transferrin (Tf), albumin (HSA) and immunoglobulins G (IgG). Eluted proteins were monitored by UV spectrometry (278 nm), while Ru species were quantified by post-column isotope dilution inductively coupled plasma mass spectrometry (ID-ICP-MS). Binding kinetics of chlorido (1) and pta complex (2) to serum proteins was followed from 5 min up to 48 h after incubation with human serum. Both Ru complexes interacted mainly with HSA. Complex (1) exhibited faster and more extensive interaction with HSA than complex (2). The equilibrium concentration for complex (1) was obtained 6 h after incubation, when about 70% of compound was bound to HSA, 5% was associated with IgG, whereas 25% remained unbound. In contrast, the rate of interaction of complex (2) with HSA was much slower and less extensive and the equilibrium concentration was obtained 24 h after incubation, when about 50% of complex (2) was bound to HSA and 50% remained unbound.